ЛІЦЕНЗУВАННЯ ЯК СПОСІБ ДЕРЖАВНОГО РЕГУЛЮВАННЯ ГОСПОДАРСЬКОЇ ДІЯЛЬНОСТІ: АНАЛІЗ СТАНУ ЗАКОНОДАВСТВА - Лісніча, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
The article analyzes the modern state of legal regulation of the licensing procedure of business activity types. A comparison study of the licensing procedure was conducted taking into consideration the recent changes in the legislation, and the implemented changes were critically evaluated.